2005
DOI: 10.1177/1558925005os-1400404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Processing Conditions on Melt Blown Web Structure. Part III — Water Quench

Abstract: The overall goal of our recent research has been to quantitatively measure the influence of commercial processing variables on the structure of polypropylene melt blown webs. In this paper, we applied a cool water quench spray to fibers to increase their thermal quenching rate. Then, we collected webs and measured single fiber diameter, shot content, fiber bundle size, basis weight uniformity and pore structure. The structure of webs produced with and without quenching was compared to access the influence of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The web consisting of finer fibers usually had a better BWU. In the study of Bresee et al, finer fibers were usually observed in the higher air jet velocity. The pores between finer fibers were evenly distributed in the fibrous web.…”
Section: Resultsmentioning
confidence: 86%
“…The web consisting of finer fibers usually had a better BWU. In the study of Bresee et al, finer fibers were usually observed in the higher air jet velocity. The pores between finer fibers were evenly distributed in the fibrous web.…”
Section: Resultsmentioning
confidence: 86%
“…The fiber orientation and basis weight of the entire web can be obtained by analyzing each image. This instrument was termed as “WebPro” and was extended to calculate additional structural parameters, including pore size, fiber diameter, and even shot formation. Similarly, Wang developed an automatic system called “Beion” to capture the web structure. Beion could fuse the images shot at different field depths to form one image.…”
Section: Fiber Formation Mechanism Experimentsmentioning
confidence: 99%
“…The extension test is an indirect method of fiber orientation measurement, in which the ratio of strength MD /strength CD represents the fiber orientation. Another common method is the use of image analysis software, including WebPro and ImageJ. , , However, there were issues with the use of the ImageJ software in estimating the fiber orientation in the SEM images in Feng’s work . In the said work, a straight line parallel to the x -axis of the sample was drawn, and the angle formed between the fiber in the ordering direction and x -axis was measured.…”
Section: Fiber Formation Mechanism Experimentsmentioning
confidence: 99%
“…Shots are generally attributed to the breakage of the fibers as they are being drawn in the air stream [3,4,18,75,89,148,149,163,164,165]. Butin with Lohkamp (1973) suggested that shot is created from elastic "snap back" when fiber broke [165].…”
Section: Generation Of Small Isolated Spherical Particlesit Is Supposmentioning
confidence: 99%